2017
DOI: 10.1016/j.jmb.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periplasmic Chaperones and Membrane Thickness on BamA-Catalyzed Outer-Membrane Protein Folding

Abstract: The biogenesis of outer-membrane proteins (OMPs) in gram-negative bacteria involves delivery by periplasmic chaperones to the β-barrel assembly machinery (BAM), which catalyzes OMP insertion into the outer membrane. Here, we examine the effects of membrane thickness, the Escherichia coli periplasmic chaperones Skp and SurA, and BamA, the central subunit of the BAM complex, on the folding kinetics of a model OMP (tOmpA) using fluorescence spectroscopy, native mass spectrometry, and molecular dynamics simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
100
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 86 publications
(188 reference statements)
21
100
1
1
Order By: Relevance
“…In an alternative model, it has been proposed that the Bam complex facilitates the membrane integration of folded or partially folded β barrels by perturbing the lipid bilayer (Noinaj et al ., 2013 ). This model is supported by evidence that at least some OMPs begin to fold prior to membrane integration (Ieva et al ., 2008 ;Lee et al ., 2016 ;Sikdar et al ., 2017 ), that BamA lowers the kinetic barrier for OMP insertion imposed by lipid head groups (Gessmann et al ., 2014 ), that BamA exerts a greater catalytic effect on OMP folding in thicker bilayers (Schiffrin et al ., 2017 ), and that BamA is highly dynamic in liposomes (Doerner and Sousa, 2017 ). The crystal structure of the Bam complex shows that the POTRA domains and the four lipoproteins form a ring below the BamA β barrel.…”
Section: Introductionmentioning
confidence: 99%
“…In an alternative model, it has been proposed that the Bam complex facilitates the membrane integration of folded or partially folded β barrels by perturbing the lipid bilayer (Noinaj et al ., 2013 ). This model is supported by evidence that at least some OMPs begin to fold prior to membrane integration (Ieva et al ., 2008 ;Lee et al ., 2016 ;Sikdar et al ., 2017 ), that BamA lowers the kinetic barrier for OMP insertion imposed by lipid head groups (Gessmann et al ., 2014 ), that BamA exerts a greater catalytic effect on OMP folding in thicker bilayers (Schiffrin et al ., 2017 ), and that BamA is highly dynamic in liposomes (Doerner and Sousa, 2017 ). The crystal structure of the Bam complex shows that the POTRA domains and the four lipoproteins form a ring below the BamA β barrel.…”
Section: Introductionmentioning
confidence: 99%
“…SurA binds unfolded OmpX with low affinity (K d,app of ~800 nM), as measured by microscale thermophoresis (MST) ( Supplementary Fig. 8), similar to the affinity of SurA for other OMPs 28,43,44 . SurA-OmpX complexes were assembled by rapid dilution of urea-denatured OmpX into a solution of SurA (final concentrations: 5 µM OmpX, 5 µM SurA, 0.24 M urea) (see Methods) immediately prior to crosslinking with DSBU.…”
Section: Sura Binds Its Omp Substrates At Multiple Interaction Sitesmentioning
confidence: 58%
“…Despite its key role in OMP biogenesis and bacterial virulence 51,52 , how SurA binds its OMP substrates both specifically, but weakly 28,44,49 , and how it is able to protect its clients from aggregation and deliver them to BAM for folding into the OM, remain poorly understood in molecular detail. Previous NMR studies have shown that OmpX, tOmpA and FhuA are dynamically disordered when bound to SurA 40 -42 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the free energy of Skp3 binding to OmpC is -20 kcal·mol -1 , which supports the ideas that Skp3 is a superior holdase 17 and de-aggregation agency 6 to OMPs. Since the binding energy is so large, the release of the substrates from Skp may need the help of LPS 35,36 , DegP 2,37 or BAM system 38,39 , ensuring the direction of OMPs transportation towards the final destination.…”
Section: Discussionmentioning
confidence: 99%